TINGKAT STRES DENGAN KEJADIAN INSOMNIA PADA MAHASISWA SKRIPSI - Batmomolin, Santa A; Rumampuk, Vonny H. Rumampuk; Angela Laka (Lasalle Health Journal, 2024)
Background: Insomnia is a sleep disorder that is usually experienced by students because of pressure so that the quality and quantity of sleep is disturbed. Insomnia can occur when a person experiences stres due to pressure and insomnia is usually experienced by final year students who are writing a thesis. This sleep problem is accompanied by complaints of difficulty falling asleep at night and difficulty maintaining sleep. Aim: This study was to determine the relationship between stres levels and the incidence of insomnia that occurred in students who were writing a thesis. Method: This type of research is quantitative research using a cross-sectional approach. The population of this study was 8th semester students who were writing their theses totaling 108 respondents and the sampling technique was a total sampling of 108 respondents, with the instrument used being a questionnaire. The statistical test used was the Chi-Square test. Outcome: The significance value shows that there is a relationship between stress levels and the incidence of insomnia in students who are writing their theses. Conclusion: There is a significant correlation between stres levels and the incidence of insomnia in students who are writing a thesis.